Helping Jobseekers with Recommendations Based on Skill Profiles or Past Experience: Evidence from a Randomized Intervention - Mirjam Bächli; Rafael Lalive; Michele Pellizzari (CESifo GmbH, 2025)
Searching for jobs is challenging, and online platforms now often offer tailored job recommendations. In a randomized controlled trial with over 1,250 participants, we evaluate recommendations based on prior experience or based on skill profiles assessed at study enrolment. We find that, on average, both types of recommendations improve job finding rates. Profile-based recommendations are particularly effective for individuals with limited experience and mismatch in the prior job, while experience-based recommendations may slow down job finding for those with limited experience but a well-matched previous job. These findings highlight the need to align job search advice with jobseekers' skills.
Keywords: J24; J62; J64; 330; jobseekers; online job search; job recommendations